MINIMIZING THE RISK FACTORS FOR LOW BACK PAIN IN THE CREATIVE INDUSTRY WORKERS - Yamtana Yamtana; Heru Subaris Kasjono; Adib Suyanto (Green Publisher, 2023)
Low back pain (LBP) felt in the anatomical area of ??a person's body is affected by a load or pressure outside the tolerance limit, with various variations in the length of time the pain complaint process occurs. This pain is felt in the lumbar or lumbo-sacral area. Workers in the batik industry may be at risk of LBP caused by work activities, such as bending, repetitive or monotonous movements, using work equipment and a non-ergonomic work environment. This study aims to minimize the risk factors for LBP in batik creative industry workers. The population of this study were all batik artisans in the written batik industry in Wukirsari Village, Imogiri District, Bantul Regency, Yogyakarta Special Region, totaling 1,021 people. The sample of this study was obtained by random sampling, to determine the sample using a lottery number and the name of the batik maker, totaling 60 batik people. The inclusion criteria for the sample of this study included female gender, writing batik work, working sitting using a chair. The sample consisted of a treatment group and a control group, each consisting of 30 batik makers, hereinafter referred to as respondents. The research instruments include: meter, microthoice, scales, chair, batik hurdle, and NBM questionnaire. Ergonomic work chair design for batik size: height of seat holder = 30 cm; length of seat holder = 40 cm; seat width = 37 cm; high back of chair = 43 cm; seat back width = 37 cm. Modification of batik gawangan is to redesign batik gawangan, material from bamboo diameter of about 3 cm, with size: height = 88 cm, width = 158 cm, 4-legged pieces, equipped with 3 watt LED lights. The results of the NBM in the treatment group decreased skeletal muscle complaints into criteria: low 96.7% and moderate 3.3%. The control group had skeletal muscle disorders criteria: low 23.3%, moderate 46.7%, high 20% and very high 10%. While the results of the t-test from the NBM data each of the 30 respondents between the treatment group and the control group, the value of p = 0.000 means that there are significant differences between respondents who use chairs and ergonomic modification modifications with respondents who use dingklik and gawangan which is old. The conclusion is that the use of chairs and modifications of the ergonomic batik wrestling can minimize the risk factors for LBP in the workers of the written batik creative industry